A role for hippocampal and midbrain neural processing in context-dependent spatial memory - Puryear, Corey Brown (My University, 2008)
The ability to discriminate contextual situations is central for organisms to predict events and the outcome of behavior. This function is thought to be the byproduct of an allocentric spatial reference framework generated by the hippocampus. It is commonly assumed that hippocampal place cells (i.e., neurons that are activated when the animal occupies a particular location in the environment; the place field), underlie this function. However, it has been difficult to ascertain which aspects of hippocampal place fields are critical to perform spatial memory tasks. By recording hippocampal place cell activity while rats performed a hippocampal-dependent spatial memory task, I demonstrated that the overall specificity of place fields appears to be critical for spatial memory functions. Specific hippocampal representations of the context may be sculpted by the neuromodulator dopamine released from the ventral tegmental area (VTA). Although the activity of VTA dopamine neurons is thought to signal an error in the prediction of salient events (particularly rewards) within a given context, it has not been demonstrated that VTA neural activity is modulated by contextual information. Therefore, I recorded the activity of VTA neurons as rats performed a similar spatial memory task under varying contextual conditions. I found that the activity of reward-related VTA neurons was, indeed, gated by contextual information and exhibited reward prediction error-related activity when rewards were unexpectedly altered. However, it appeared that not all of these were dopamine neurons. This is consistent with recent reports that dopamine neurons may not generate prediction errors, per se, but may be generated by 'upstream' brain areas. Therefore, I recorded the activity of neurons in the mesencephalic reticular formation (MRNm), which sends excitatory (i.e., glutamatergic) inputs to VTA. I discovered that the majority of MRNm neurons exhibited reward-related activity and that they displayed prediction error-related activity similar to VTA neurons. Together, this dissertation provides new evidence that MRNm may, at least participate with VTA in signaling other brain areas, such as hippocampus, that expected consequences of behavior have changed. This likely enables a new representation of the context to be formed and stored into long-term memory.
Thesis (Ph. D.)--University of Washington, 2008.
Keywords: Theses--Psychology